Análise do gerenciamento dos resíduos de serviços de Saúde no Hospital Veterinário do UNIFEOB-São João da Boa Vista - Santamarina, Anderson (2011)
This study aims at investigating the variables that influence the implementation and feasibility of a Waste Menagement Program at Health Case Facilities (WMPHCF) on the perspective of solid waste generated by the Veterinary Hospital of the University Center of Octavio Bastos Colleges, and specifically for use in our fiels of study. With this instrument we believe we are fulfilling the essentially preventive mission in order to anticipate the major health problems.